Effect of Threshold Inspiratory Muscle Training on Functional Fitness and Respiratory Muscle Strength Compared to Incentive Spirometry in Children and Adolescents With Obesity: A Randomized Controlled Trial - Phatthareeda Kaeotawee; Kanokporn Udomittipong; Akarin Nimmannit; Prakarn Tovichien; Apinya Palamit; Pawinee Charoensitisup; Khunphon Mahoran (Frontiers Media S.A., 2022)
BackgroundTo determine the effect of threshold inspiratory muscle training (IMT) on functional fitness and respiratory muscle strength (RMS) compared to incentive spirometry (IS) in children/adolescents with obesity.MethodsA total of 60 obese children/adolescents aged 8-15 years were randomized into the threshold IMT group (n = 20), the IS group (n = 20), or the control group (n = 20). The IMT group performed 30 inspiratory breaths with the intensity set at 40% of baseline maximal inspiratory pressure (MIP) twice daily for 8 weeks; the IS group performed 30 breaths with sustained maximum inspiration twice daily for 8 weeks; and, the control group was assigned no training device for 8 weeks. Six-min walk test (6-MWT), RMS, and spirometry were compared between baseline and 8 weeks.ResultsSix-MWT distance (528.5 ± 36.2 vs. 561.5 ± 35.2 m, p = 0.002) and MIP (121.2 ± 26.8 vs. 135.3 ± 32.1%Predicted, p = 0.03) were significantly improved after 8 weeks of IMT training. There was no significant difference in any evaluated pulmonary function parameters between baseline and 8 weeks in the IS or control groups; however, 6-MWT distance demonstrated a trend toward significant improvement in the IS group (526.9 ± 59.1 vs.549.0 ± 50.6 m, p = 0.10). No significant difference among groups was found for any variable relative to change from baseline to post-training.ConclusionEight weeks of threshold IMT training significantly improved both inspiratory muscle strength (MIP) and functional fitness (6-MWT) in children/adolescents with obesity. Eight weeks of IS training yielded a trend toward significantly improved functional fitness.